Glacier Changes across Northern Ellesmere Island - White, Adrienne (Université d'Ottawa / University of Ottawa, 2019)
This thesis investigates the causes and patterns of glacier and ice shelf changes across Northern Ellesmere Island, including rapid recent changes to marine-terminating glaciers and the mass balance of the Milne Ice Shelf along Ellesmere Island’s northern coastline. The first part describes the change in the areal extent of 1773 glacier basins across northern Ellesmere Island between ~1999 and ~2015 that were measured from optical satellite imagery. The results show that the regional ice coverage decreased by 1705.3 km2 over the ~16-year period, a loss of ~5.9%. This indicates a marked acceleration compared to the 3.4% loss recorded by Sharp et al. (2014) between ~1960 and ~2000. Ice shelves had the greatest losses relative to their size, of ~42.4%. Glaciers feeding into ice shelves reduced in area by 4.7%, while tidewater glaciers reduced in area by 3.3%. Marine-terminating glaciers with floating ice tongues reduced in area by 4.9% and 19 of 27 ice tongues disintegrated, causing these glaciers to retreat to their grounding lines. Land-terminating glaciers lost 4.9% of their 1999 area, including the complete loss of three small ice caps (<1.5 km2). These changes indicate the high sensitivity of the ice cover of northern Ellesmere Island to recent climate warming, and that continued losses are likely to occur in the future. In particular, the ice masses most susceptible to further losses are marine-terminating glaciers with floating termini and small land-terminating ice caps at low elevations. To further investigate the forcings leading to the recent losses of floating ice tongues, the second part focuses on marine-terminating glacier changes in the Yelverton Bay region of northern Ellesmere Island since 1959. From 1959-2017, the total ice tongue area decreased by 49.07 km2, with the majority of this loss occurring from 2005-2009 (34.68 km2). The loss of ice tongues since 2005 occurred when open water replaced multi-year landfast sea ice and first-year sea ice in the regions adjacent to the ice tongues. These changes were accompanied by an increase in mean annual mid-depth (i.e., 100 and 200 m) ocean temperatures from -0.29°C from 1999-2005 to 0.67°C from 2006-2012. Despite the recent return of ocean temperatures to below pre-2006 levels, atmospheric summer temperatures have continued to rise (+0.15°C decade-1 between 1948 and 2016), with open water continuing to occur. This suggests that loss of buttressing from sea ice appears to be the primary control on ice tongue losses, with air and ocean warming important in weakening the sea ice and ice tongues, together with offshore wind events in some years. Based on current climate it is unlikely that ice tongues will reform in the future. To examine the stability of the remaining ice shelves, the Milne Ice Shelf was selected as a case study to analyse the processes and patterns of surface mass balance. In 2008 a mass balance network of eight stakes was established across the Milne Ice Shelf and over the past 10 years has revealed a mean annual surface mass balance of -0.33 ±0.04 m water equivalent yr-1. Comparison of this surface mass balance rate with past ice thickness change measurements made by Mortimer et al. (2012) indicate that recent thinning may be limited to the surface, and accelerating over time. Individual stake and snow measurements reveal a surface mass balance gradient, whereby ablation decreases with proximity to the seaward edge of the ice shelf. The ablation gradient is driven by the microclimatology recorded at three automatic weather stations installed along the ice shelf, which show that air temperature and solar radiation decreases towards the coastline, while snow accumulation increases. Climate analysis suggests that the entire Milne Ice Shelf is in a state of negative mass balance in years with >200 melting degree days (MDD), while the one net positive balance year (in 2013) occurred when MDD totals were 105 yr-1. Although the Milne Ice Shelf is the most stable remaining ice shelf along the northern coast of Ellesmere Island, the relationship between climate and mass balance, along with a recent increase in calving along its landward margins, indicate that it is out of equilibrium with current climate. Overall, the ice coverage across northern Ellesmere Island is shrinking. The land-terminating ice that formed under cooler climatic conditions of the past, particularly low-lying small ice caps, are out of equilibrium with current climatological conditions. In addition, recent changes in the ice tongues and ice shelves demonstrate that the northern coastline of Ellesmere Island is approaching a future where the permanent floating ice cover can no longer be sustained.
Keywords: Glaciers; Ice Shelves; Arctic; Ellesmere Island